PERAN PENDIDIKAN DAN KAMPANYE DIGITAL DALAM MENINGKATKAN KESADARAN LINGKUNGAN GENERASI Z - Satria, Farhan (Cendekia Madani Nusantara, 2025)
This study explores how education and digital campaigns in enhancing environmental awareness among Generation Z. Using a literature review method, the study analyzes previous research, policy reports, and relevant examples of digital campaign practices. The findings indicate that formal and non-formal education supported by interactive digital campaigns can strengthen knowledge, attitudes, and pro-environmental practices among Generation Z. The synergy between educational strategies and digital campaigns should be developed to achieve broader behavioral change. This article is formatted in MS Word following the Cemara Journal template, including margin, font, and structure guidelines.